Análisis factorial del estilo de vida de los miembros de la iglesia adventista del séptimo día del distrito misionero de Víctor Larco de Trujillo, 2009 - Torres Armas, Elías Alberto (2010)
ABSTRACT The present research allowed determining the key factors in the lifestyle of members of the Seventh –day-Adventist Church of Víctor Larcos´s missionary district of Trujillo, 2009, that attend meetings and participate in all activities. From the data collected through a stratified random sample with proportional allocation of 127 members and characteristics analyzed by factorial analysis of multiple correspondence and classifications. The results indicated three main factors: A factor practices a lifelong, a factor practices eventual and the other one practices an indifferent and spontaneous Adventist lifestyle. Most of them believe in prophecy, God and act with faith; they guard on Saturday and spend time with their family, planning their incomes and outcomes, have a full trust in divine power, no alcohol and tobacco consumption, make a rational use of electricity, they are happy collaborators and ready for the service, living in own home, work, joined to the church under the influence of the family, friends and neighbors; they have TV, DVD, radio, iron, fridge, washing machine, blender, but don´t have cleaner/polisher, microwave oven, rice cooker, microcomputer, others. They are grouped into three classes: Adapted-warm, Conservatives-lukewarm, and Modest-cold.